KRITIK KONSEP POLIGAMI DALAM DRAFT KHI PERSPEKTIF METODOLOGI SYAHRUR - Muharram, Tamyiz (Al-Mawarid Jurnal Hukum Islam, 2006)
The formulating of poligamy in KHI draft based on the goal of shariâah. Departing from this, the basic principle of marriage in Islam is monogamy. Shahrur justifies poligamy as stated in Surat an-Nisaâ verse 3. This verse according to Shahrur including hududiyah, either hudud al-kamm or hududul kaif. While, according to KHI draft, it is impossible for husband to conduct the justice in term of poligamy, and then Shahrur stated that the verse of poligamy constitutes the theory of limits, either al-had al-adna or al had al-adna. Hence, poligamy permits but not more than 4 wives.